THE SCIENTIFIC SUBSTANTIATION OF THE TERM OF PASSENGER CARS OPERATION - Loboiko, L. M.; Myamlin, S. V.; Pulariia, A. L. (Science and Transport Progress, 2008)
For passenger coaches the scientific bases on substantiation of the operation time with the account of their technical conditions and separation of the inter-repair cycles for coaches with different repair amounts are developed.